High-quality health systems in the Sustainable Development Goals era: time for a revolution - Kruk, M; Gage, A; Arsenault, C; Jordan, K; Leslie, H; Roder-Dewan, S; Adeyi, O; Barker, P; Daelmans, B; Doubova, S; English, M; Elorrio, E; et al. (Elsevier, 2018)
Although health outcomes have improved in low-income and middle-income countries (LMICs) in the past several decades, a new reality is at hand. Changing health needs, growing public expectations, and ambitious new health goals are raising the bar for health systems to produce better health outcomes and greater social value. But staying on current trajectory will not suffice to meet these demands. What is needed are high-quality health systems that optimise health care in each given context by consistently delivering care that improves or maintains health, by being valued and trusted by all people, and by responding to changing population needs. Quality should not be the purview of the elite or an aspiration for some distant future; it should be the DNA of all health systems. Furthermore, the human right to health is meaningless without good quality care because health systems cannot improve health without it.